A review of NBTI mechanisms and models. (February 2018) - Mahapatra, Souvik; Parihar, Narendra
Abstract: A comprehensive review is done of different NBTI mechanisms and models proposed in the literature over the past years. The Reaction-Diffusion (RD) model based comprehensive framework and the alternative Energy Well (EW) models are discussed. The model capabilities to simultaneously predict the temporal kinetics of stress and recovery are evaluated. Key experimental signatures that support or refute model assumptions are highlighted.